ASSOCIATION REPORTS FOR THE YEAR 1943. - Blough, Carman G.; Bailey, George D.; Gilman, Stephen; Paton, William A.; Chamberlain, H. T.; Littleton, A. C.; Rorem, C. Rufus; Dixon, Robert L. (The Accounting Review, 1944)
Abstract The article presents information about a Committee appointed by the American Accounting Association. The work of the Committee on Monographs during the year, 1943, has been devoted primarily to two projects. The first consisted of preparing a compilation of the releases and pronouncements on accounting matters issued by the Securities and Exchange Commission, the Committee on Accounting Procedure and the Committee on Auditing Procedure of the American Institute of Accountants. The second project was the preparation of a monograph on the principles of consolidated statements. This monograph was written by Dr. Maurice Moonitz of Stanford University, and was reviewed and approved for publication by the Committee. The Committee has also given some attention to two or three other projects and manuscripts. The president of the Committee said that the educational institutions and programs are all being subjected to special stresses and difficult restrictions during the war. The programs of most colleges and universities in fields customarily followed by men have had to be materially curtailed or completely eliminated.